The Christmas Season as a Risk Factor for Chronic Obstructive Pulmonary Disease Exacerbations - Neil W Johnston; Andrew McIvor; Kim Lambert Reg N; Justina M Greene; Pat Hussac; Maria Gerhardsson de Verdier; Tim Higenbottam; Jonathan Lewis; Paul Newbold; Athula Herath; Martin Jenkins (Canadian Respiratory Journal)
BACKGROUND: Epidemics of hospitalization for chronic obstructive pulmonary disease (COPD) occur annually during the Christmas holidays, and COPD exacerbations commonly coincide with respiratory viral infections.